2016
DOI: 10.1080/00918369.2016.1151697
|View full text |Cite
|
Sign up to set email alerts
|

Homophobic Attitudes and Associated Factors Among Adolescents: A Comparison of Six Latin American Countries

Abstract: Homophobic attitudes are still very common in the world, although there are large differences between countries. This study analyzed the responses of almost 30,000 8th- and 9th-grade students from six countries who participated in the Latin American component of the International Civic and Citizenship Education Study. Higher levels of homophobia were found in the Dominican Republic, Guatemala, and Paraguay than in Chile, Colombia, and Mexico. Homophobic attitudes were positively associated with being male, hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 32 publications
4
16
0
9
Order By: Relevance
“…Demographic characteristics also play a role in explaining SOGIP. Men, in general, display higher levels of SOGIP than women (e.g., Chaux & Léon, 2016;Haney, 2016;Lee & Cunningham, 2016;Monto & Supinski, 2014;Romero, Morera, & Wiebe, 2015). This sex effect was corroborated in an analysis of attitudes toward homosexuality in 79 countries, which furthemore demonstrated that being older (vs. younger), having lower levels of education (vs. higher levels), lower levels of income/social status (vs. higher levels), and being married (vs. being unmarried), predicted higher levels of SOGIP (Jäckle & Wenzelburger, 2015).…”
Section: Determinants Of Sogipmentioning
confidence: 99%
“…Demographic characteristics also play a role in explaining SOGIP. Men, in general, display higher levels of SOGIP than women (e.g., Chaux & Léon, 2016;Haney, 2016;Lee & Cunningham, 2016;Monto & Supinski, 2014;Romero, Morera, & Wiebe, 2015). This sex effect was corroborated in an analysis of attitudes toward homosexuality in 79 countries, which furthemore demonstrated that being older (vs. younger), having lower levels of education (vs. higher levels), lower levels of income/social status (vs. higher levels), and being married (vs. being unmarried), predicted higher levels of SOGIP (Jäckle & Wenzelburger, 2015).…”
Section: Determinants Of Sogipmentioning
confidence: 99%
“…Encouraging tolerance for different groups in society is therefore commonly regarded as important elements of civic and citizenship educational policies across Latin American countries have revealed considerable emphasis on encouraging students to demonstrate tolerance toward diversity (Ainley, Schulz, & Friedman, 2013). One prominent example is the Colombian Program of Citizenship Competencies (Colombian Ministry of Education, 2004;Chaux, Lleras, & Velásquez, 2004), which includes a content dimension encompassing pluralism, identity, and respect for diversity as well as issues related to discrimination and exclusion.…”
Section: Students' Acceptance Of Social Minoritiesmentioning
confidence: 99%
“…The influence of the Church over sociopolitical affairs also constitutes a barrier to distributing condoms and sex education, both at school and in the home environment (Djellouli and Quevedo-Gómez 2015). These effects are compounded by anti-lesbian, gay, bisexual and transgender discourses and HIV-related prejudice prevalent across various Christian dominations in Latin America (Djellouli and Quevedo-Gómez 2015;Chaux and León 2016). HIV stigma is a barrier to HIV testing.…”
Section: Hiv Among Latin American Gay and Bisexual Menmentioning
confidence: 99%